2003
DOI: 10.1046/j.1460-9592.2003.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative blood salvage and postoperative reinfusion of drained blood during surgical correction of craniosynostosis in infants

Abstract: Our results suggest that the postoperative use of the CBCII ConstaVac(R) system is as efficient as the perioperative use of the CATS(R) system for reducing homologous blood transfusion during repair of craniosynostosis in infants weighing <10 kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…18,29 For this reason, it is important to reduce the transfusion rate in the endoscopic as well as in the open remodeling procedures. Because dilution may play an important role in the drop in postoperative hemoglobin level, 9 and a very strict protocol for the administration of intravenous fluids postoperatively was incorporated in 2012, resulting in a significant decline in transfusion rate to 7.7% in EACS-treated patients.…”
mentioning
confidence: 99%
“…18,29 For this reason, it is important to reduce the transfusion rate in the endoscopic as well as in the open remodeling procedures. Because dilution may play an important role in the drop in postoperative hemoglobin level, 9 and a very strict protocol for the administration of intravenous fluids postoperatively was incorporated in 2012, resulting in a significant decline in transfusion rate to 7.7% in EACS-treated patients.…”
mentioning
confidence: 99%
“…Serious or fatal transfusion-related reactions occur in 3/10,000 units given. 26 Although blood products are routinely tested for infectious agents, there is still a risk of transmission of blood-borne infections such as HIV (1/200,000) and hepatitis B and C (1/30,000 for each virus). Risks also include bacterial contamination, acute hemolytic reactions (1/250,000), TRALI (1/5000), and TRIM.…”
Section: Discussionmentioning
confidence: 99%
“…Risks also include bacterial contamination, acute hemolytic reactions (1/250,000), TRALI (1/5000), and TRIM. 10,26 Studies have reported EBL as high as 60%-100% of estimated blood volume (EBV) with almost all patients undergoing a blood transfusion during or immediately after the surgery. 16,32,34 Our results were consistent with the high EBL presented in previous studies, with a 15 ml/kg average EBL (18% EBV) for the C group and 23.5 ml/kg (29% EBV) for the protocol group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the feasibility of this technique is not clearly established, Orliaguet and colleagues compared CATS intraoperative blood salvaging with the postoperative use of the CBCII Consta Vac system in a retrospective nonrandomized study [43]. They found the postoperative blood salvaging system was equally effective as the perioperative use of the CATS system for reducing homologous blood transfusion during craniosynostosis repair in infants weighing less than 10 kg.…”
Section: Perioperative Blood Salvagementioning
confidence: 99%